Zullobalanus santamariaensis sp. nov., a new late Miocene barnacle species of the family Archaeobalanidae (Cirripedia: Thoracica), from the Azores - Winkelmann, Kai; Buckeridge, John S.; Costa, Ana Cristina; Dionísio, Maria Ana Manso; Medeiros, André; Cachão, Mário; Ávila, Sérgio P. (Zootaxa, 2010)
A new species of Archaeobalanidae barnacle is described from the late Miocene and early Pliocene of Santa Maria Island (Azores). Samples were collected primarily from outcrops at Malbusca and “Pedra-que-Pica”. Zullobalanus santamariaensis sp. nov. is endemic to the Azores archipelago and until the discovery of this material, the genus was known only from the Southern Hemisphere. For such a long-range distribution we assume a combination of planktotrophic larval development, sea-surface oceanic currents and transport by cetaceans. This study endorses the elevation of the subgenus Zullobalanus to generic level.